Pola Komunikasi Pada Upacara Adat Lampung Begawi Cakak Pepadun Di Desa Blambangan Kabupaten Lampung Utara - Nur Fitriani, Selly; Kartika, Tina; Ashaf, Abdul Firman (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This study aims to determine the processions in Begawi Cakak Pepadun and to analyze the communication patterns that occur in the series of event. The study was located in Blambangan Village, North Lampung Regency, a village with a majority of Lampung Pepadun people who continue to uphold their traditional customs, especially in held of Begawi Cakak Pepadun.. The communication patterns in Begawi Adat Cakak Pepadun encompass several components, including the participants, the content of the message, the recipients of the message, and the media used. All these elements combine to form a unique communication pattern. This study employs a descriptive method with a qualitative approach, involving five informants. Data collection techniques include interviews, observations, and documentation. Data analysis is conducted through data reduction, data presentation, and data verification. The findings indicate that the communication patterns during the events are divided into two models: a multi-directional communication pattern observed in the processes of pemandai, manjau, ngedio, cangget, and cakak pepadun, and a one-way communication pattern evident in the turun mandei process.